Assessment of the unwanted tooth movement associated with an extended maxillary fixed retainer (3D analysis) - Mohamed H. Abbas; Essam M. Abdalla; Eiman S. Marzouk; Nadia M. El Harouni (BMC Oral Health, 2024)
Abstract Background Posttreatment changes after orthodontic treatment are challenging. One of the main reasons for such a phenomenon is the lack of patient compliance with removable retainers especially in the maxillary arch, due to palatal coverage, deterioration of speech, decreased masticatory efficiency, and loss of retainers. Fixed retainers have been introduced to overcome patient compliance and provide longer stable results. However, teeth still show movements when a six-unit fixed retainer is in place. Thus, in this study, an eight-unit fixed retainer was evaluated in an attempt to eliminate unwanted movements. The aim of this research was to assess short-term positional changes associated with an eight-unit extended maxillary fixed retainer. Materials and methods A single-arm clinical trial was conducted to address the aim of the study. This research was approved by the institutional review board of the Faculty of Dentistry, Alexandria University (IORG:0008839, No-0479–8/2022). The registration date of this study was 5/06/2023. Twenty-eight patients (19.8 ± 4.5 years) who had finished the active orthodontic phase and started retention had an eight-unit extended maxillary fixed retainer that was bonded to the palatal surface of the maxillary incisors, canines, and the first premolars or the second premolars. Pre-retention and one-year post-retention intra-oral scans were made to produce STL files that were superimposed to determine the amount of tooth change. Additionally, analysis of digital casts and lateral cephalometric radiographs was performed. Results Statistically significant changes in all planes and the rotation of teeth after one year of retention were found. The upper right lateral incisor exhibited the most evident change in the vertical plane, while the upper right central incisor exhibited the greatest change overall. Minimal changes in the cast measurements were observed. Lateral cephalometric measurements showed minimal changes after one year of retention, and these changes were not statistically significant except in the interincisal angle and the angle between the upper incisor and the line connecting the A-point to the pogonion. Conclusion Increasing the extension of maxillary fixed retainers did not eliminate unwanted tooth movement in the first year of retention.